Selection of tool-hole size and development of cranial implants for Ti Gr.2 perforated sheet during the flexible die-less forming process - Gurpude R.; Mulay A.; Sharma P. (My University, 2025)
Single-point incremental forming is a versatile and flexible technology for manufacturing sheet metal components in small series. However, SPIF in the biomedical field can be difficult because there are many challenges. One of the main issues is controlling the settings of the process and making sure the components meet the required size standards for production. The primary goal of this study is to determine the impact of various process parameters on the formability of perforated titanium grade 2. The geometrical parameters, such as tool and hole diameters, were initially investigated for the formability of sheet material. Later, SPIF parameters, such as toolpath, feed, and step depth, were varied at three levels, and the part responses were recorded in terms of roughness, maximum temperature, and angle of failure. The results reveal that the hole diameter, tool diameter, and surface roughness, respectively, are significant factors for formability and the highest temperature attained during the process. It is found that surface roughness begins to decrease as the tool diameter increases for the perforated sheet. The hole diameter of 10 mm and tool diameter of 4.5 mm is found to be used optimal combination. The cranial implants were prepared with optimal tool-hole diameters combinations, and all sound parts were evaluated for roughness, thickness deviation, and accuracy. The cranial implant, formed with follow-periphery, feed rate of 300 mm/min, and a step depth of 0.2 mm, results in sound part with improved forming accuracy and a reduction in surface roughness. The variation in microstructure and hardness for base and optimally formed sample were also investigated. © The Author(s), under exclusive licence to The Brazilian Society of Mechanical Sciences and Engineering 2024.